MENINGKATKAN KOMPETENSI GURU DALAM MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) MELALUI SUPERVISI AKADEMIK - Kamsi Kamsi (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
This research is motivated by a lack of teacher competency in preparing a plan for implementing learning. This can be seen, the teacher does not design a plan for implementing the learning itself and the teacher is not able to provide an evaluation of what has been taught. It is not uncommon for teachers to teach improperly (carelessly taking responsibility). The purpose of this study is to improve teacher competency in preparing a learning implementation plan. This study uses the School Action Research design. School Action Research is carried out in four stages, namely planning, implementation, observation and reflection, and carried out at least in two cycles. The results of the study prove that the assessment of the implementation plan for the learning of the Melayu Besar Elementary School 001 teachers in class IV and class V increased by 6 points or 30%. Whereas for the 002 Melayu Besar state Primary School in the fourth grade increased by 7 points or 35% and for class V increased by 5 points or 25%. Based on the results of the above research, researchers can conclude that by applying academic supervision can improve teacher competency in developing plans for implementing learning in the Melayu Besar 001 Elementary School and the Melayu Besar 002 Public Elementary School